Advances in chemical sensing technologies for VOCs in breath for security/threat assessment, illicit drug detection, and human trafficking activity. (17th January 2018) - Giannoukos, S; Agapiou, A; Taylor, S
Abstract: On-site chemical sensing of compounds associated with security and terrorist attacks is of worldwide interest. Other related bio-monitoring topics include identification of individuals posing a threat from illicit drugs, explosive manufacturing, as well as searching for victims of human trafficking and collapsed buildings. The current status of field analytical technologies is directed towards the detection and identification of vapours and volatile organic compounds (VOCs). Some VOCs are associated with exhaled breath, where research is moving from individual breath testing (volatilome) to cell breath (microbiome) and most recently to crowd breath metabolites (exposome). In this paper, an overview of field-deployable chemical screening technologies (both stand-alone and those with portable characteristics) is given with application to early detection and monitoring of human exposome in security operations. On-site systems employed in exhaled breath analysis, i.e. mass spectrometry (MS), optical spectroscopy and chemical sensors are reviewed. Categories of VOCs of interest include (a) VOCs in human breath associated with exposure to threat compounds, and (b) VOCs characteristic of, and associated with, human body odour (e.g. breath, sweat). The latter are relevant to human trafficking scenarios. New technological approaches in miniaturised detection and screening systems are also presented (e.g. non-scanning digital light processing linear ion trap MS (DLP-LIT-MS), nanoparticles, mid-infrared photo-acoustic spectroscopy and hyphenated technologies). Finally, the outlook for rapid and precise, real-time field detection of threat traces in exhaled breath is revealed and discussed.